2014
DOI: 10.1111/trf.12771
|View full text |Cite
|
Sign up to set email alerts
|

A systematic study of single‐nucleotide polymorphisms in the A4GALT gene suggests a molecular genetic basis for the P1/P2 blood groups

Abstract: The results of this investigation demonstrate a consistent association of A4GALT SNPs rs2143918 and rs5751348 with the P1/P2 phenotypes and suggest that SNP rs5751348 may lead to allelic variations in A4GALT gene expression and consequently leads to the formation of the P1/P2 phenotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 29 publications
7
29
0
Order By: Relevance
“…Although the combined frequency and serologic approach for P1 expression identified four NT changes, this could simply be due to linkage disequilibrium, which, in theory, could be addressed with a larger sample size. Indeed, a recent publication identified these same four NT changes associated with P1, but one (rs66781836) was later excluded in an uncommon sample with haplotype recombination between the possible NT changes . To optimize exclusion among strongly linked SNPs, mining of large‐scale genomic data sources for examples where one or more of the linked NT changes occur independently and performing targeted follow‐up serologic typing could be employed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the combined frequency and serologic approach for P1 expression identified four NT changes, this could simply be due to linkage disequilibrium, which, in theory, could be addressed with a larger sample size. Indeed, a recent publication identified these same four NT changes associated with P1, but one (rs66781836) was later excluded in an uncommon sample with haplotype recombination between the possible NT changes . To optimize exclusion among strongly linked SNPs, mining of large‐scale genomic data sources for examples where one or more of the linked NT changes occur independently and performing targeted follow‐up serologic typing could be employed.…”
Section: Discussionmentioning
confidence: 99%
“…In 2001, it was shown that A4GALT encodes a 4‐α‐galactosyltransferase enzyme, which adds α‐galactose to paragloboside to create the P1 antigen . In 2011 and 2014, it was reported that the single‐nucleotide polymorphisms (SNPs) designated rs8138197, rs2143918, and rs5751348 correlated with P1+/P1– expression, but the mechanism remained unknown. There was uncertainty as to the actual SNP responsible, but recently Westman et al showed that SNP rs5751348 (NT G > T) is located in a RUNX1 transcription factor binding region that controls the expression of P1 with chromosomal location chr22:43,113,793G associated with the P1+ phenotype and chr22:43,113,793 T with P1–.…”
mentioning
confidence: 99%
“…For each genetic marker, we established PCR-SSP methods according to a standard protocol [23] and with primers listed in table 1. The A4GALT SNP rs2143918 has a 100% correlation with the P 1 /P 2 phenotype in all populations, except for rare individuals of African descent [24]. This SNP was addressed for P genotyping.…”
Section: Methodsmentioning
confidence: 99%
“…Despite several attempts, the molecular background of the P1PK blood group system is still not fully elucidated. Several authors have shown that the expression levels of A4GALT mRNA is higher in P 1 than in P 2 , and there is a general agreement that the upregulated transcript may cause increased production of Gb3/CD77 synthase [1820]. However, despite finding several SNPs associated with P 1 /P 2 status, no credible mechanism for allelic variation in A4GALT gene expression has been proposed.…”
Section: Introductionmentioning
confidence: 99%